NUMERICAL STUDY OF HEAT AND MASS TRANSFER OPTIMIZATION IN A 3-D INCLINED SOLAR DISTILLER - Ghachem, Kaouther; Maatki, Chamseddine; Kolsi, Lioua; Alshammari, Naif; Öztop, Hakan Fehmi; Borjini, Mohamed Naceur; Al-Salem, Khaled (Vinca Inst Nuclear Sci, 2017)
A numerical study of the 3-D double-dffusive natural convection in an inclined solar distiller was established. The flow is considered laminar and caused by the interaction of thermal energy and the chemical species diffusions. The governing equations of the problem, are formulated using vector potential-vorticity formalism in its 3-D form, then solved by the finite volumes method. The Rayleigh number is fixed at Ra = 10(5) and effects of the buoyancy ratio and inclination are studied for opposed temperature and concentration gradients. The main purpose of the study is to find the optimum inclination angle of the distiller which promotes the maximum mass and heat transfer.
Keywords: solar distiller; 3-D study; double-diffusive convection; cavity inclination